Application of daily routine management in the purchasing sector in an import and export company - Assis, Luiz Felipe Oliveira de; Servare Junior, Marcos Wagner Jesus (Brazilian Journal of Production Engineering, 2021)
This paper was designed to demonstrate how daily routine management influences the performance of the purchasing department. From the action-research method, applied in an export and import company based in the city of Vitória, Espírito Santo - Brazil, a series of corrections was implemented in the existing processes and new ones were included in the operational routine of the sector using tools such as BASICO matrix, which impacted directly and indirectly on the other departments of the company that helped in the execution of the adopted strategies. The main bottlenecks that the sector had before the implementation of the DRM and the results after the application of the methodology were added, summarized in cost reduction, improvement and reliability of processes and, finally, greater customer satisfaction.